ANALYSIS OF MAJOR CYBER ATTACKS ON DEFI IN 2024 AND COUNTERMEASURES - Semerenska, Viktoriia (Collection of scientific papers «ΛΌГOΣ», 2025)
The decentralized finance (DeFi) ecosystem experienced significant growth in 2024, accompanied by a rise in sophisticated cyberattacks. This article analyzes key security incidents, including the PenPie reentrancy attack, flash loan exploits on Radiant Capital and Goledo Finance, a social engineering breach at Concentric Finance, a multi-signature compromise on Orbit Chain, and phishing campaigns targeting Binance users. Detailed technical insights and countermeasures, such as reentrancy guards, decentralized oracles, and enhanced user authentication, highlight strategies for mitigating risks and strengthening DeFi security.